Exploring Psychological Well-Being in Practitioners of Success Rituals - Alwi Mahardhika Sodiq; Mochamad Widjanarko; Suharsono Suharsono (Haluan Sastra Budaya, 2025)
Pesugihan is a mystical ritual carried out by individuals in secret and unreasonable to obtain wealth involving mystical rituals of shamanic practices. The purpose of this research is to find out the psychological dynamics and how to interpret an individual who performs the pesugihan ritual. Data exploration was carried out by analyzing the basic motivations, both intrinsic and extrinsic, from the practice of pesugihan rituals including the informants' feelings when carrying out various rituals, praying, meditating, and fasting. The methodology in this study uses descriptive qualitative with a phenomenological approach. There were three informants who were involved in the research, through purposive sampling. Techniques in collecting data using observation and interviews. The results in this study indicate that psychological well-being is found in informants who carry out the pesugihan ritual and bring up an understanding of local beliefs which have a positive impact in the form of a holy feeling of soul, a feeling of comfort, a healthy body, a brighter appearance, a clearer mind, and a calmer worried mind.